Avaliação da influência da ativação ultrassônica na alteração do pH de cimentos obturadores. - Fantini, Mariana Burachi [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
The aim of this study was to compare the pH of MTA Fillapex® and Sealapex cements, after shaking with ultrasound. Both cements have an alcaline pH, alkalinity of MTA Fillapex® coming from MTA cytotoxicity, while Sealapex cements has its alkalinity coming from the presence of calcium hydroxide in its composition, generating a high solubility. Inturn, the high solubility releases more calcium ions in the tissue, leaving the pH of the alcaline cement. The test was carried out in accordance with the ISO6876: 2012 standard. Fifty polyethylene tubes (n=10) were made and one of the inlets was sealed with utility wax. The tubes were filled with MTA Fillapex and Sealapex cements. Five groups were formed: MTA Fillapex without agitation, MTA Fillapex with ultrasonic agitation, Sealapex without agitation, Sealapex with ultrasonic agitation and one group the tubes were kept empty for control. The cements of the ultrasound group were agitaled with Irrisonic insert attached to the Ultra Sonic Piezoeletric Ultrasound for 20 seconds. After the setting time the samples were individually immersed in tubes with deionized water and stored in an oven. The pH was measured at 10 minutes, 24 hours, 7, 15, 21 and 30 days after being stirred. The data obtained were submitted to statistical analysis by the SigmaPlot 12.0 program, using Kruskal-Wallis, with a 5% significance level. Both studied cements showed an increase in pH with the use of ultrasound, and MTA Fillapex cement showed an increase in alkalinity after 24 hours. Therefore, the ultrasonic activation of the MTA Fillapex and Sealapex filling cements favored the increase in pH levels, which may be favorable for the success of endodontic treatment.

O objetivo deste estudo foi comparar o pH dos cimentos MTA Fillapex® e Sealapex, após agitação com ultrassom. Ambos os cimentos apresentam pH alcalino, sendo a alcalinidade do MTA Fillapex® proveniente da citotoxicidade do MTA, enquanto que o cimento Sealapex tem sua alcalinidade proveniente da presença de hidróxido de cálcio em sua composição, gerando uma alta solubilidade. Por sua vez a elevada solubilidade libera mais íons de cálcio no tecido, deixando o pH do cimento alcalino. O teste foi realizado de acordo com a norma ISO6876: 2012. Cinquenta tubos de polietileno (n=10) foram confeccionados e uma das embocaduras foi vedada com cera utilidade. Os tubos foram preenchidos com os cimentos MTA Fillapex e Sealapex. Foram formados 5 grupos: MTA Fillapex sem agitação, MTA Fillapex com agitação ultrassônica, Sealapex sem agitação, Sealapex com agitação ultrassônica e um grupo os tubos foram mantidos vazios para controle. Os cimentos do grupo ultrassom foram agitados com inserto Irrissonic acoplada no Ultrassom Piezoelétrico Ultra Sonic por 20 segundos. Após o tempo de presa, as amostras foram imersas individualmente em tubos com água deionizada e armazenadas em estufa. O pH foi mensurado em 10 minutos, 24 horas, 7, 15, 21 e 30 dias após serem agitadas. Os dados obtidos foram submetidos à análise estatística pelo programa SigmaPlot 12.0, utilizando Kruskal-Wallis, com nível de significância de 5%. Ambos os cimentos estudados mostraram elevação do pH com a utilização do ultrassom, sendo que o cimento MTA Fillapex apresentou aumento da alcalinidade a partir de 24 horas. Sendo assim, a ativação ultrassônica dos cimentos obturadores MTA Fillapex e Sealapex favoreceu o aumento dos níveis de pH, podendo ser favorável para o sucesso do tratamento endodôntico.
Evaluation of the influence of ultrasonic activation on solubility and pH change in feling cements.
Keywords: Root canal obturation; Ultrassom; Obturação do canal radicular; Endodontia